ORGANIZATION OF THE DISPATCHER'S AUTOMATED WORKPLACE - Sayat , Г.А.; Iskakov , М.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The problem of automation of production processes and management processes as a tool for improving labor is always relevant. The sphere of Informatization increases the importance of computer technology in management processes. At the present stage of enterprise management automation, the most promising is the automation of management functions directly installed at the workplaces of specialists. Such systems are widely used in organizational enterprise management, called automated workplaces. In particular, as a result of automation of the transport dispatcher's workplace, the integrated system allows you to collect, analyze, calculate data and generate accounting documentation to provide better and more complete information on this area. The article provides for the organization of an automated workplace of the dispatcher. The principle of building an automated workplace is analyzed and the algorithm of the model operation is developed based on the analysis of an automated workplace requirements and tasks.